Provenance Lost and Found: Alfred Bourguignon - Voukelatos, John (KOINON: The International Journal of Classical Numismatic Studies, 2018)
On the 22nd October 2017 the Swiss numismatic firm Nomos offered at auction a silver didrachm minted by the Campanian city of Nola. Unbeknownst to the auction house this coin was once in the collection of Alfred Bourguignon. Although little is known about this 19th century collector, he is recorded by the Almanach de Gotha as being the deputy of the Netherlands Consulate in Naples. He was also a partner in the prominent 19th century Neapolitan bank, Banca Meuricoffre, founded by Achilles Meuricoffre and continued by his two sons Oscar and Tell; he was also their distant cousin. The Meuricoffre (German Moerikhofer) were wealthy Swiss bankers who immigrated to Naples in 1760 to facilitate trade with the Kingdom for the fine silk of Calabria. To repay large financial debts Alfred Bourguignon had accrued from casino and horse gambling, he repeatedly embezzled the bank bringing it to bankruptcy. Although Alfred Bourguignon died in September 1903, Banca Meuricoffre continued trading until 1905 by which time it was insolvent and went into liquidation. The financial damage brought to the Meuricoffre family was significant, having to sell warehouses, agricultural land, the apartment of Palazzo Caprioli, and the Casa Grande of Capodimonte, and an estate in Ischia. The financial activities of the bank were subsequently transferred to Credito Italiano, which opened in Naples in July 1905.